Answer:
Yes. See explanation below.
Explanation:
If (x + 1) is a factor of P, this would mean that x +1 = 0, x = -1 is a zero of the equation given by the polynomial.
So we're going to evaluate x = -1 to see if it's a zero
![x^(3)+x^(2) -10x-10 =(-1)^3+(-1)^2-10(-1)-10= -1+1+10-10=0](https://img.qammunity.org/2020/formulas/mathematics/high-school/int586kovyrzrfx2b451xd23urqb3ib8ms.png)
Therefore, when we evaluate x = -1 the polynomial has a result of zero and thus we can conclude that (x +1) is one of the factors of P.